The perceptions of women’s roles and progress: a study of Malay women - Abdullah, Kalthom; Mohd. Noor, Noraini; Wok, Saodah (Springer, 2008)
This study examines the general perceptions of women towards their roles, their interpretation of progress, as well as the facilitating factors and barriers to their progress. Questionnaires were distributed to 1,000 Malay women in Malaysia from rural and urban areas, from various age and income groups. Interviews were also carried out on the selected sample. Using both quantitative and qualitative methods of analyses, the results showed that women were perceived to play a strong, influential, and supportive role in their families. The results also showed how women perceive progress. These findings are discussed in relation to culture, socialization, values and norms of the Malay society.